How universities can better engage with the animation/VFX sector in Scotland. Issue 1 (1st December 2018) - Mortimer, Jonathan
This research explores how universities can better engage with the animation/VFX industry in Scotland, by examining what skills current industry requires of graduates, and how institutes can better collaborate with working studios. Given the unknown impact that Brexit may have on the animation/VFX sector both nationally and further afield, now more than ever should the education sector re-evaluate how to bridge the gap for graduates moving on from education to being a productive member of the industry. Animation studios were invited to share their opinions and thoughts on the current state of the animation/VFX sector in Scotland, and to discuss how industry could make better use of universities. Industry wants to collaborate with education, to inspire and encourage talent development for the animation/VFX sector in Scotland. Both the education and animation/VFX sectors have their own unique methodologies and approaches for working and communicating with one another, which at times can be counterproductive. Education must change its relationship with industry, in favour of a more symbiotic relationship, by inviting industry to play a more active role in course design and structure, as a means for institutes to keep the contents of their courses relevant and be able to respond to the current skills requirement of industry.